Whole-brain monosynaptic outputs and presynaptic inputs of GABAergic neurons in the vestibular nuclei complex of mice - Shi, Xun-Bei; Wang, Jing; Li, Fei-Tian; Zhang, Yi-Bo; Qu, Wei-Min; Dai, Chun-Fu; Huang, Zhi-Li (Frontiers in Neuroscience, 2022)
GABAergic neurons in the vestibular nuclei (VN) participates in multiple vital vestibular sensory processing allowing for the maintenance and rehibilitation of vestibular functions. However, although the important role of GABA in the central vestibular system has been widely reported, the underlying neural circuits between VN GABAergic neurons and other brain functional regions remains elusive, which limits the further study on the underlying mechanism. Hence, it is necessary to elucidate neural connectivity based on outputs and inputs of GABAergic neurons in the VN. This study employed a modified rabies virus retrograde tracing vector and cre-dependent adeno-associated viruses (AAVs) anterograde tracing vector, combined with a transgenic VGAT-IRES-Cre mice, to map the inputs and outputs of VN GABAergic neurons in the whole brain. We found 51 discrete brain regions received projections from VN GABAergic neurons in the whole brain, and there were 77 upstream nuclei innervating GABAergic neurons in the VN. These nuclei were mainly located in four brain regions, including medulla, pons, midbrain, and cerebellum. Among them, VN GABAergic neurons established neural circuits with some functional nuclei in the whole brain, especially regulating balance maintenance, emotion control, pain processing, sleep and circadian rhythm regulation, and fluid homeostasis. Therefore, this study deepens a comprehensive understanding of the whole-brain neural connectivity of VN, providing the neuroanatomical information for the further research on neural mechanism of the co-morbidities with vestibular dysfunction.